2012
DOI: 10.1016/j.tube.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in antioxidant pathway: Risk factors for hepatotoxicity in tuberculosis patients

Abstract: SummaryTuberculosis (TB) treatment can cause serious sequelae including adverse effects such as anti-TB drug-induced hepatotoxicity (ATDH). We performed a candidate gene-based association study between single nucleotide polymorphisms (SNPs) in 10 genes in the antioxidant pathway and ATDH susceptibility. The subjects comprised 100 Japanese patients with pulmonary TB who received a treatment regimen including isoniazid and rifampicin. Out of them, 18 patients had ATDH. Thirty-four tag SNPs in 10 genes were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 41 publications
1
58
0
Order By: Relevance
“…Studies have shown that the predisposing factors of susceptibility to ATDH mainly comprise environmental and genetic factors, especially the latter (Chen et al, 2015). These genetic factors, such as NAT2, BACH1, TNF, and ABCB1, are involved in the pharmacokinetics of drugs including metabolism, transport, and immune and antioxidant responses (Yimer et al, 2011;Kim et al, 2012;Nanashima et al, 2012;Du et al, 2013). Studies have shown that TXNRD1-mediated antioxidant function protects the liver against oxidative injury, and the genetic variations in TXNRD1 are related to DILI (Minami et al, 2005;Zidek et al, 2007;Kwon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the predisposing factors of susceptibility to ATDH mainly comprise environmental and genetic factors, especially the latter (Chen et al, 2015). These genetic factors, such as NAT2, BACH1, TNF, and ABCB1, are involved in the pharmacokinetics of drugs including metabolism, transport, and immune and antioxidant responses (Yimer et al, 2011;Kim et al, 2012;Nanashima et al, 2012;Du et al, 2013). Studies have shown that TXNRD1-mediated antioxidant function protects the liver against oxidative injury, and the genetic variations in TXNRD1 are related to DILI (Minami et al, 2005;Zidek et al, 2007;Kwon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Non-genetic factors include female sex, race, and environmental factors such as alcohol intake (Pande et al, 1996;Lee et al, 2002;Marra et al, 2007;de Castro et al, 2010). The genetic factors are involved in drug metabolism, transport, and immune and antioxidant responses, and include N-acetyltransferase 2 (NAT2), BTB and CNC homology 1 (BACH1), tumor necrosis factor-a (TNF) and adenosine triphosphate binding cassette B1 (ABCB1) (Yimer et al, 2011;Kim et al, 2012;Nanashima et al, 2012;Du et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, association of polymorphisms in Nacetyltransferase 2 (NAT2) (Cho et al, 2007;Du et al, 2013;Huang et al, 2002;Ohno et al, 2000;Possuelo et al, 2008;Yimer et al, 2011), cytochrome P450 family-2 subfamily-E member-1 (CYP2E1) Huang et al, 2003;Vuilleumier et al, 2006), glutathione S-transferases M1 (GSTM1) (Huang et al, 2007;Li et al, 2013;Roy et al, 2001), uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) (Chang et al, 2012), ATP-binding cassette subfamily-B member-1 (ABCB1) (Yimer et al, 2011), solute carrier organic anion transporter family member-1B1 (SLCO1B1) (Chen et al, 2015a;Li et al, 2012), mitochondrial superoxide dismutase (SOD2) (Huang et al, 2007), and nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway (Nanashima et al, 2012) genes with antituberculosis DIH has been reported previously.…”
Section: Candidate Gene Association Studiesmentioning
confidence: 99%
“…Considering the importance of lung lesion progression and the extra-pulmonary dissemination of bacilli in TB pathogenesis, it was suggested that treatment with antioxidant drugs could be beneficial as an adjunct to anti-tuberculosis drug therapy. An added benefit of antioxidant treatment of patients with TB is the reduction of the toxic side effects of antituberculosis drug therapy, mediated in part by the generation of oxygen free radical in the liver 7 . These observations led us to propose that the combination of antioxidant activity and mtCAs inhibition might result in novel anti-tubercular agents with dual mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%